2008
DOI: 10.1002/nme.2452
|View full text |Cite
|
Sign up to set email alerts
|

An explicit method with improved stability property

Abstract: SUMMARYA new explicit method is presented. This method has an enhanced stability property when compared with the previously published explicit method (J. Eng. Mech. 2007; 133(7):748-760), which is unconditionally stable for linear elastic and any instantaneous stiffness softening systems based on linearized analysis whereas it is only conditionally stable for any instantaneous stiffness hardening system. In contrast to the previously published explicit method, the most important improvement of the new explicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…0 are found for i = 1; 2; 3; ::: for a linear elastic system. The development details of this method are similar to those of the previously published algorithms [17,18] and, thus, they will not be elaborated on herein. In this derivation, the proof of convergence must be conducted rst.…”
Section: Proposed Family Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…0 are found for i = 1; 2; 3; ::: for a linear elastic system. The development details of this method are similar to those of the previously published algorithms [17,18] and, thus, they will not be elaborated on herein. In this derivation, the proof of convergence must be conducted rst.…”
Section: Proposed Family Methodsmentioning
confidence: 99%
“…The structure-dependent integration method was rst developed by Chang in 2002 [15]. Some integration methods of this type were also successfully developed by Chang [16][17][18][19][20][21][22] subsequently. These structure-dependent integration methods can simultaneously integrate the major advantages of the implicit and explicit algorithms, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been also shown that the numerical dispersion and energy dissipation characteristics of this family of methods are the same as those of the generalized-α method (Chung and Hulbert 1993). The most important property of KRM is controllable numerical dissipation when compared to the currently available structure-dependent integration methods (Chang 1997(Chang , 2002(Chang , 2007(Chang , 2009(Chang , 2010Chen and Ricles 2008) except for the Chang-α dissipative method (Chang 2014(Chang , 2015. The controllable numerical dissipation can be used to suppress the spurious oscillations of high frequency modes, while the low frequency modes can be integrated very accurately.…”
Section: Introductionmentioning
confidence: 91%
“…Note that the spectral decomposition technique to analytically obtain the numerical solution is generally not used for a general step-by-step integration procedure (Chang, 1997(Chang, , 2000(Chang, , 2002(Chang, , 2007(Chang, , 2009(Chang, , 2010Hilber et al, 1977;Newmark, 1959;Sha et al, 2003;Tamma et al, 2001Tamma et al, , 2003Zhou and Tamma, 2004). In fact, a computer program is usually applied to conduct the stepby-step integration to yield the numerical solution.…”
Section: Numerical Displacement Responsesmentioning
confidence: 98%